2021
DOI: 10.3390/metabo11080520
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect of Noodles Containing Fermented Lettuce Extracts

Abstract: The aim of the current study was to examine the antidiabetic effect of noodle containing fermented lettuce extract (FLE) on diabetic mice as a pre-clinical study. The γ-aminobutyric acid (GABA) content, antioxidant capacity, and total polyphenol content of the FLE noodles were analyzed and compared with those of standard noodles. In addition, oral glucose and sucrose tolerance, and fasting blood glucose tests were performed using a high-fat diet/streptozotocin-mediated diabetic mouse model. Serum metabolite pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…33 In addition, Jeong et al showed that the intake of noodles containing fermented lettuce extract decreased the glucose level and insulin resistance in mice with diabetes induced by intraperitoneal injection of streptozotocin. 34 Similar results were observed in our study, where HFD10 had a significantly lower insulin level and HOMA-IR index, suggesting that the 10% concentration of RLP had a powerful effect on insulin signaling. It is possible that this effect is caused by the content of fiber and polyphenols contained in the different varieties of lettuce as demonstrated by the study of Cheng et al 29 In vitro studies have shown inhibitory effects on the digestive enzymes α amylase and α-glucosidases by polyphenols present in plants, fruits, or leaves as well as inhibition of glucose transporters (SGLT1 and GLUT2) may also contribute to the marked effect on postprandial glucose and insulin response observed.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…33 In addition, Jeong et al showed that the intake of noodles containing fermented lettuce extract decreased the glucose level and insulin resistance in mice with diabetes induced by intraperitoneal injection of streptozotocin. 34 Similar results were observed in our study, where HFD10 had a significantly lower insulin level and HOMA-IR index, suggesting that the 10% concentration of RLP had a powerful effect on insulin signaling. It is possible that this effect is caused by the content of fiber and polyphenols contained in the different varieties of lettuce as demonstrated by the study of Cheng et al 29 In vitro studies have shown inhibitory effects on the digestive enzymes α amylase and α-glucosidases by polyphenols present in plants, fruits, or leaves as well as inhibition of glucose transporters (SGLT1 and GLUT2) may also contribute to the marked effect on postprandial glucose and insulin response observed.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…Results showed that there were no significant differences among all four groups at week 0, but the blood glucose levels for HFD-NS5% and HFD-NS10% remained lower compared with HFD . In addition, Jeong et al showed that the intake of noodles containing fermented lettuce extract decreased the glucose level and insulin resistance in mice with diabetes induced by intraperitoneal injection of streptozotocin …”
Section: Resultsmentioning
confidence: 99%
“…Another previous study has investigated the anti-diabetic effect of noodles containing fermented lettuce extract in diabetic mice. Noodles with fermented lettuce extract were high in γ-aminobutyric acid content, antioxidant capacity, and total polyphenol content, demonstrating that mice fed this noodle had lower blood sugar levels and insulin resistance than mice fed standard noodles [ 21 ]. This study suggested the antioxidant role of fermented lettuce extract in menopausal syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that tartary buckwheat fermented with L. plantarum TK9 and L. paracasei TK1501 has the potential to regulate blood glucose in diabetics. Antidiabetic effects of fermented lettuce extracts were studied by Jeong et al ( 2021 ). This study indicates fermented lettuce extract could be considered an effective additive to diabetic foods to balance blood glucose levels and improve insulin resistance.…”
Section: Fermentation In the Food Industry As An Environmentally Frie...mentioning
confidence: 99%